Strategic Innovation and Performance of FinTech Enterprises in Ondo State, Nigeria - Oludoyi, Isaac Olakunle; Adesuyi, Isaac; Yusuf, Jamiu Adeniyi (Indonesian Journal of Banking and Financial Technology, 2024)
The study focused on strategic innovation (product innovation, technological innovation and marketing innovation) and performance (customer satisfaction, trust and customer retention) of Fintech enterprises in Ondo State, Nigeria. The study adopted the survey research design. The data was analysed using the Statistical Package for the Social Sciences (SPSS) and the result was presented in tables using frequency, percentages, mean and standard deviation (descriptive statistics). Multiple regression (inferential statistics). Findings from the study reveals that strategic innovation have a positive significant influence on customer satisfaction, customer trust and customer retention. Thus, the study concluded that strategic innovations are necessary for Fintech enterprises in Ondo State to optimize performance. The study recommends that Fintech enterprises should continually engage in strategic innovations to optimize performance.